Narratological Analysis of Temporality in Novel - Nasr M. A. Abdulrraziq; Ayman E. M. Geedallah (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This paper definitely attempts to intermingle them with regard to structural analysis. It adopted the theory of Gerard Genette, the analysis of the famous novel Great Expectations by Charles Dickens, the main discussion concerns order and duration whereas frequency is ruled out. Consequently, order can be presented by two different narrative techniques; through the profound analysis of analepsis and prolepsis to show the chronological and anachronological order of the novel. A further analysis of the novel also includes the alternation of the four narrative movements of duration which are divided into techniques of deceleration; descriptive pause and scene whereas techniques of accelerations; ellipsis and summary. The diagrams and tables of the study aim to reach semi-statistical deduction for the chronological techniques of anachronism and its effect on the structure of the narrative time of the novel as whole, which gives a general idea about the system of the time in novel.